822 Local radiotherapy synergizes with tumor-specific TCR redirected T cells in the rejection of prostate cancer. (10th December 2020) - Catucci, Marco; Basso, Veronica; Deantoni, Chiara Lucrezia; Baroni, Simone; Spinelli, Antonello; Freschi, Massimo; Cozzarini, Cesare; Fiorino, Claudio; Muzio, Nadia Di; Formenti, Silvia; Demaria, Sandra; Mondino, Anna
Abstract : Background: Adoptive T cell therapy (ACT) has become a promising option for cancer patients. While tumor-infiltrating lymphocytes were initially exploited as a source of tumor reactive lymphocytes, T cells genetically redirected to the tumor by TCR/CAR gene transfer are now in clinical validation. In the case of solid tumors, unfavorable immunosuppressive microenvironments remain recognized barriers to therapeutic efficacy. We have recently reported that the therapeutic activity of ACT against poorly immunogenic and indolent prostate cancer is improved by the concurrent targeting of the tumor stroma by mean of T cells redirected to an ubiquitously expressed minor histocompatibility antigen or a tumor vessel targeted TNF derivative. We have now taken the concept further and hypothesized that local radiotherapy (RT), might also synergize with ACT by promoting lymphocyte endothelial transmigration and tumor recognition, and ultimately favor abscopal effects. Methods: We investigated the combination of local RT and ACT in TRAMP (Transgenic Adenocarcinoma of the Mouse Prostate) mice and in mice bearing subcutaneous B16/B16-OVA (MO4) or TRAMP-C2/TRAMP-C2-OVA tumors. Local RT was delivered by X-RAD SmART (the Small Animal Radiation Therapy) microirradiator in single dose or hypo-fractioned regimens. ACT consisted of T cells engineered with tumor-specific TCRs. Immunogenic consequences were analyzed by Real-Time PCR, and flow cytometry (FACS) analyses. Prostate tumor debulking was evaluated by histological analyses. Results: We found that local hypofractionated RT and ACT, while individually inefficacious in controlling tumor growth, concurred to the debulking of advanced prostate adenocarcinoma when used in combination in treating TRAMP mice. Mechanistically, exposing isolated tumor cells, or the TRAMP mouse prostate to hypo-fractionated RT regimens induced stronger type-I interferon (IFN-I) responses, when compared to single high dose. Acutely, hypofractionated RT promoted better immune tumor infiltration, among which TCR redirected effector cells. Conclusions: Data support feasibility and efficacy of combining hypo-fractionated local RT with ACT in the form of TCR engineered T cells to promote prostate cancer recognition and eradication. Tumor debulking was observed in the absence of treatment-related toxicity. Systemic recirculation of TCR redirected T cells was observed. We are now investigating therapeutic effects at distal (metastatic) sites. Acknowledgements: The authors acknowledge the support of the Italian Association for Cancer Research (AIRC) Ethics Approval: The studies involving animals were approved by The Institutional Ethical Committee (IACUC#999).